Pengaruh Model Discovery Learning Berbasis Proyek Green Chemistry terhadap Hasil Belajar dan Keterampilan Kolaborasi Siswa - Sefhira Aulia; Dewi Syafriani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the effect of a green chemistry project-based discovery learning model on students' learning outcomes and collaboration skills in acid-base learning. This study used a quasi-experimental design with a pretest-posttest control group design in two randomly selected classes. The research instruments included a learning outcome test (pretest-posttest) and a collaboration skills observation sheet. Data were analyzed using the N-Gain test, independent sample t-test, and effect size calculation. The results showed that the N-Gain value of the experimental class was 0.66 ± 0.15, higher than the control class's 0.44 ± 0.14. Hypothesis testing showed a sig. <0.05 for learning outcomes and collaboration skills, indicating a significant difference between the two classes. In addition, the effect size values ​​obtained were 0.61 (moderate category) for learning outcomes and 0.96 (high category) for collaboration skills. These findings prove that the green chemistry project-based discovery learning model is effective in improving students' learning outcomes and collaboration skills, and have implications for the development of more contextual and collaborative chemistry learning.